Effectiveness Of Strategy Of Preference Pyramid In Achievement Of Science Of Second Intermediate Grade Students - Hussein Ali al-Jubouri, Hamziyah; Dawood Ali Al-Jubouri, Salam (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to identify effectiveness of the strategy of preference pyramid in achievement of science subject of second intermediate grade students and to investigate the following null hypothesis: There is no statistically significant difference at the level of significance (0.05) between the scores mean of students of the experimental group who studied the subject of science in the strategy of pyramid of preference and the scores mean of achievement of students of the control group who studied the same subject in the usual method. To investigate the research hypothesis, the two researchers chose an experimental design partially controlled , the current research community was all students of second intermediate grade in Al-Diwaniyah Governorate for the academic year (2017-2018) , the research sample consisted of (42) students from the second intermediate-grade students from Al-Mi’raj School for Boys in the General Directorate of Diwaniyah Education , (21) Students for the experimental group who studied according to the strategy of preference pyramid and (21) students in the control group who studied according to the usual method. To achieve the aims of the research, an achievement test was prepared of (45) objective item (multiple choice), the total test score was (45), and the validity of the content has been confirmed for testing and calculation of reliability using Cronbach’s alpha equation.